Structural analysis of power augmented guide vane for the vertical axis wind turbine / Amin Kazemzadeh - Amin, Kazemzadeh (2012)
This report illustrates the static structural analysis of the power augmented guide vane (PAGV) performed by the finite element (FE) method. The results obtained can be used to apply the PAGV in the real environmental conditions. As part of the equatorial regions, Malaysia experiences low and unsteady wind speed. Most of the areas experience a wind speed, which is lower than 4 m/s for most hours. Thus, the PAGV is designed to overcome the inferior aspect of low wind speed in Malaysia by guiding and increasing the speed (almost 1.7 times) of high altitude free-stream wind from all directions before entering the wind turbine. The vertical axis wind turbine (VAWT) was chosen and enclosed by the PAGV, so this can minimize the current problems of wind energy such as bird strike, the noise pollution and electromagnetic interference. In fact, the PAGV is a multipurpose appliance, which the solar panel can be laid on its top surface. It can also collect the rain water by directing the rain water to flow towards the center of the system where the water is stored in a storage tank for general use. In this research, the static structural analysis of the PAGV has been carried out by using ANSYS software. The pressure distribution and wind speed that flows through the PAGV have been analyzed and simulated by using ANSYS Fluent software. The simulation results for the PAGV of the wind speed of 60 m/s showed minimum safety factor of 1.7 for the specified materials. However, the simulation showed that a disagreeable large deflection occurred at the middle of each vanes of the PAGV, which reaches maximum 9.46 mm. By introducing a new support system, an attempt has been done to improve the initial design. Also, the problem of large deflection is expected be removed in the proposed support system.